2021
DOI: 10.1038/s41467-020-20604-3
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B inhibition reduces disease severity in autoimmune blistering diseases

Abstract: Pemphigoid diseases refer to a group of severe autoimmune skin blistering diseases characterized by subepidermal blistering and loss of dermal-epidermal adhesion induced by autoantibody and immune cell infiltrate at the dermal-epidermal junction and upper dermis. Here, we explore the role of the immune cell-secreted serine protease, granzyme B, in pemphigoid disease pathogenesis using three independent murine models. In all models, granzyme B knockout or topical pharmacological inhibition significantly reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 60 publications
2
63
0
Order By: Relevance
“…Furthermore, granzymes A and B contributed to LPS-induced cell shedding in a perforin-independent manner, providing strong evidence that gd IELs facilitate cell shedding through a mechanism other than direct lysis. Extracellular granzyme has been shown to promote the proteolytic cleavage of ECM proteins such as laminin, type IV collagen, and fibronectin, which are found in the intestinal BM [53][54][55][56][57][58][59] . This has been shown to contribute to cell death, as GzmB-mediated matrix remodeling can induce the detachment and apoptosis of cultured endothelial and transformed epithelial cells 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, granzymes A and B contributed to LPS-induced cell shedding in a perforin-independent manner, providing strong evidence that gd IELs facilitate cell shedding through a mechanism other than direct lysis. Extracellular granzyme has been shown to promote the proteolytic cleavage of ECM proteins such as laminin, type IV collagen, and fibronectin, which are found in the intestinal BM [53][54][55][56][57][58][59] . This has been shown to contribute to cell death, as GzmB-mediated matrix remodeling can induce the detachment and apoptosis of cultured endothelial and transformed epithelial cells 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular granzyme has been shown to promote the proteolytic cleavage of ECM proteins such as laminin, type IV collagen, and fibronectin, which are found in the intestinal BM 53-58 . Extracellular GzmB was recently shown to cleave α 6 integrin, a component of the hemidesmosome that is critical in anchoring epithelial cells to the BM 59 . Moreover, circulating lymphocytes have been shown to secrete GzmA and B in order to remodel the vascular BM and facilitate extravasation 54,55,60 .…”
Section: Discussionmentioning
confidence: 99%
“…The role played by ADAM-mediated shedding in the downregulation of BP180 during normal physiological turnover remains unclear. In pathological conditions, e.g., in linear IgA dermatosis, plasmin can cleave BP180 [93] and in BP mast cell and/or basophil-derived Granzyme B can directly degrade BP180 [132]. Neutrophil elastase has been shown to degrade hemidesmosomal BP180 in a murine model of BP [133].…”
Section: Mechanisms and Consequences Of Bp180 Downregulationmentioning
confidence: 99%
“…121 Moreover, Hiroyasu et al found that VTI-1002 could induce local inhibition of GZMB action to significantly reduce the total blistering area and could reduce disease severity in a murine pemphigoid disease (a group of severe autoimmune skin blistering diseases) model. 108 Turner et al confirmed that GZMB impaired the epithelial barrier function through Ecadherin and filaggrin cleavage, and VTI-1002 reduced the severity of skin barrier dysfunction in atopic dermatitis (the most commonly occurring inflammatory skin condition). 94 These studies suggest the therapeutic potential of VTI-1002 for GZMB-induced/aggravated diseases.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Additionally, GZMB that enters the cells mainly plays a significant role in eliminating tumour cells/virus-infected cells, [27][28][29][37][38][39][40]44 eliminating intracellular bacteria and parasites, 19,20,41,42 and viruses. [46][47][48][49][50] However, extracellular GZMB plays an important role in inducing the occurrence and development of diseases (such as inflammation, 8,84,[93][94][95][96][97][98][99] fibrosis, 88,115 CAV, 83 AAA, 89 autoimmune blistering diseases, 92,93,108 age-related macular degeneration, 16 SLE/LN, 109 RA, 4 SSPE, 110 cardiovascular disease, [112][113][114] and wound healing [117][118][119][120] ).…”
Section: Nanomaterials Delivery Systems For Gzmbmentioning
confidence: 99%